2006
DOI: 10.1007/s10815-005-9007-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraovarian arterial blood flow resistance in oligomenorrheal infertile women

Abstract: Purpose:Intraovarian arterial blood flows before and after follicular rupture in ovulation induced cycles were examined by transvaginal color flow Doppler imaging. The changes observed in the intraovarian arterial resistance before and after ovulation in relation to the regularity of menstruation and several other parameters were analyzed. Methods: In a prospective study, 22 patients undergoing infertility treatment in our center were recruited. Patients were divided into two subgroups, according to their mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, we also indicated that oligomenorrheal patients showed a disturbance in the ovulation process during the peri-ovulatory period with respect to intraovarian arterial blood flow resistance [13]. The induction of ovulation with a FSH low-dose step-up regimen improved the ovulation process of the oligomenorrheal patients with a deep decrease in intraovarian arterial blood flow resistance, and consequently, the pregnancy rate was also increased [13]. From these results, we conclude that mature oocytes with good quality develop and are ovulated when a substantial decrease in intraovarian arterial blood flow resistance occurs during the ovulation process.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, we also indicated that oligomenorrheal patients showed a disturbance in the ovulation process during the peri-ovulatory period with respect to intraovarian arterial blood flow resistance [13]. The induction of ovulation with a FSH low-dose step-up regimen improved the ovulation process of the oligomenorrheal patients with a deep decrease in intraovarian arterial blood flow resistance, and consequently, the pregnancy rate was also increased [13]. From these results, we conclude that mature oocytes with good quality develop and are ovulated when a substantial decrease in intraovarian arterial blood flow resistance occurs during the ovulation process.…”
Section: Introductionmentioning
confidence: 56%
“…This parameter is noninvasive and one of the available methods for evaluating the follicular environment during ovulation. Moreover, we also indicated that oligomenorrheal patients showed a disturbance in the ovulation process during the peri-ovulatory period with respect to intraovarian arterial blood flow resistance [13]. The induction of ovulation with a FSH low-dose step-up regimen improved the ovulation process of the oligomenorrheal patients with a deep decrease in intraovarian arterial blood flow resistance, and consequently, the pregnancy rate was also increased [13].…”
Section: Introductionmentioning
confidence: 61%
“…This was found to be useful in the evaluation of both the quality of the oocytes and in the developmental competence of the corresponding oocytes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%